Polygenic risk score for ulcerative colitis predicts immune checkpoint inhibitor-mediated colitis - Pooja Middha; Rohit Thummalapalli; Michael J. Betti; Lydia Yao; Zoe Quandt; Karmugi Balaratnam; Cosmin A. Bejan; Eduardo Cardenas; Christina J. Falcon; David M. Faleck; Princess Margaret Lung Group; Matthew A. Gubens; et al. (Nature Communications, 2024)
Abstract Immune checkpoint inhibitor-mediated colitis (IMC) is a common adverse event of treatment with immune checkpoint inhibitors (ICI). We hypothesize that genetic susceptibility to Crohn’s disease (CD) and ulcerative colitis (UC) predisposes to IMC. In this study, we first develop a polygenic risk scores for CD (PRSCD) and UC (PRSUC) in cancer-free individuals and then test these PRSs on IMC in a cohort of 1316 patients with ICI-treated non-small cell lung cancer and perform a replication in 873 ICI-treated pan-cancer patients. In a meta-analysis, the PRSUC predicts all-grade IMC (ORmeta=1.35 per standard deviation [SD], 95% CI = 1.12–1.64, P = 2×10−03) and severe IMC (ORmeta=1.49 per SD, 95% CI = 1.18–1.88, P = 9×10−04). PRSCD is not associated with IMC. Furthermore, PRSUC predicts severe IMC among patients treated with combination ICIs (ORmeta=2.20 per SD, 95% CI = 1.07–4.53, P = 0.03). Overall, PRSUC can identify patients receiving ICI at risk of developing IMC and may be useful to monitor patients and improve patient outcomes.